2021
DOI: 10.30827/publicaciones.v51i3.16709
|View full text |Cite
|
Sign up to set email alerts
|

Consecuencias del COVID-19 en los centros educativos en función de su contexto socioeconómico y titularidad

Abstract: La pandemia mundial provocada por el COVID-19 ha originado cambios en la organización y gestión de los centros educativos, en las metodologías docentes y en las relaciones que se establecen con los estudiantes y sus familias. El objetivo de esta investigación es conocer la opinión de directores y directoras de 43 centros educativos de Sevilla capital (España), sobre la gestión de sus centros y las posibles problemáticas surgidas durante el periodo de cese de actividades lectivas presenciales, teniendo en cuent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…En cuanto al tipo de instituciones que están centrando sus esfuerzos en el estudio de la superación de las desigualdades mediante tecnología, es remarcable el peso de centros de educación superior como la Universidad de Sevilla con 6 artículos (Cabero et al, 2021;Cabero et al, 2020;Cabero et al, 2019;López-Noguero et al, 2021a;López-Noguero et al, 2021b;Padilla-Carmona et al, 2016), la Universidad de Salamanca (Casillas-Martín et al, 2020;Verdugo, 2019;Romo, 2018;Casado-Muñoz et al, 2015), y la Universidad Complutense de Madrid (Tirado et al, 2021;Hernández et al, 2021;Calderón et al, 2020y Vázquez et al, 2015, con cuatro documentos cada una de ellas.…”
Section: Resultsunclassified
“…En cuanto al tipo de instituciones que están centrando sus esfuerzos en el estudio de la superación de las desigualdades mediante tecnología, es remarcable el peso de centros de educación superior como la Universidad de Sevilla con 6 artículos (Cabero et al, 2021;Cabero et al, 2020;Cabero et al, 2019;López-Noguero et al, 2021a;López-Noguero et al, 2021b;Padilla-Carmona et al, 2016), la Universidad de Salamanca (Casillas-Martín et al, 2020;Verdugo, 2019;Romo, 2018;Casado-Muñoz et al, 2015), y la Universidad Complutense de Madrid (Tirado et al, 2021;Hernández et al, 2021;Calderón et al, 2020y Vázquez et al, 2015, con cuatro documentos cada una de ellas.…”
Section: Resultsunclassified
“…The students reported that the suspension of face-to-face classes in schools generated feelings of helplessness in their families because when their homes became "educational settings", they encountered a series of unexpected difficulties such as connectivity problems, the number of computers available and the lack of necessary support to fully participate in virtual learning. Nevertheless, the participants reported that they were able to benefit from more time for leisure activities such as intensive use of cell phones and social networks with which they maintained contact with their peer groups; this was one of the main strategies used to compensate for the absence of face-to-face contact [10,11,24,34]. This coincides with the value placed at these ages on interpersonal relationships as key factors in the development of social skills and opportunities for socialization [35].…”
Section: Discussionmentioning
confidence: 99%
“…The suspension of face-to-face classes in schools significantly affected families with children at risk of social exclusion, exposing them to stressful situations that sometimes made them feel overwhelmed by the moments of uncertainty they were experiencing. All of this hindered families themselves from being able to provide optimal educational support for their children, to which was added the lack of skills to be able to advise or help in the use of digital tools as key elements to ensure pedagogical continuity [11]. The quality of learning was deficient in most occasions, which was attributed to the fact that virtual education accentuated the economic and social inequalities of students, mainly in vulnerable educational contexts, with the existence of a digital and social gap being palpable, especially in those families that lacked strategies to successfully manage the learning processes of their children [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de las posibles justificaciones está precisamente la mayor dependencia que tienen los centros públicos con respecto a las administraciones educativas en comparación a los privados. Investigaciones anteriores han mostrado que los centros públicos parecen estar en peores condiciones para afrontar la enseñanza online, debido a las carencias de recursos del alumnado y a los limitados recursos de los centros (Cabrera, 2020;López-Noguero et al, 2021;Feyen, 2020), por lo que en general, el nivel de satisfacción en las familias en cuanto a la gestión de la pandemia por parte de los centros es mucho mayor en los centros privados que en los centros públicos o concertados (Cabrera-Méndez et al, 2021). Además, cabe destacar que los centros privados orientan su acción educativa de acuerdo con su propia visión, a pesar de que esta debe estar alineada con los marcos normativos de carácter general (Capella, 2004).…”
Section: Discusión Vinculada a La Tipología De Centrounclassified